2023
DOI: 10.1042/bst20220807
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cell death: how macrophages sense neighbouring cell infection and damage

Abstract: Programmed cell death is a critical host defence strategy during viral infection. Neighbouring cells deal with this death in distinct ways depending on how the infected cell dies. While apoptosis is considered immunologically silent, the lytic pathways of necroptosis and pyroptosis trigger inflammatory responses by releasing inflammatory host molecules. All these pathways have been implicated in influenza A virus infection. Here, we review how cells sense neighbouring infection and death and how sensing shapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The pathogenesis of O. viverrini-induced inflammation is believed to be attributed to the somatic and excretory/secretory antigens released by this parasite, which stimulate and recruit inflammatory cells to the bile duct, where they reside. In addition, chemoattractant molecules and damage-associated molecular patterns along with microbial bacteria enhance or exert a synergistic effect on the attraction of inflammatory cells [24][25][26]. In hamster studies on the response to helminth infection, inflammatory cells, such as neutrophils, mononuclear cells, eosinophils, and mast cells, have been reported as common white blood cells [12,18,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of O. viverrini-induced inflammation is believed to be attributed to the somatic and excretory/secretory antigens released by this parasite, which stimulate and recruit inflammatory cells to the bile duct, where they reside. In addition, chemoattractant molecules and damage-associated molecular patterns along with microbial bacteria enhance or exert a synergistic effect on the attraction of inflammatory cells [24][25][26]. In hamster studies on the response to helminth infection, inflammatory cells, such as neutrophils, mononuclear cells, eosinophils, and mast cells, have been reported as common white blood cells [12,18,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…MLKL is transferred into the plasma membrane which leads to the efflux of potassium, resulting in activating NLRP3 intrinsically (Figure 2). 21,82,103 To prevent excessive inflammatory reactions, MQs phagocyte apoptotic bodies are infected with IV which is almost found in alveolar routes and lung tissue. However, pyroptosis and necroptosis are observed, along with the inflammation due to releasing necrotic cells and applying specific mechanisms, especially inflammasomes.…”
Section: Network Of the Inflammasome Cellular Death Pathways In IV In...mentioning
confidence: 99%
“…However, studies have shown that IV has multiple evade mechanisms that allow it to escape innate immunity. To propagate and amplify an infection, IV needs to evade the innate immune response 82,83 …”
Section: Interconnection Of Panoptosis Innate Immune Responses and In...mentioning
confidence: 99%
See 2 more Smart Citations